2003
DOI: 10.1097/01.asn.0000085590.83005.a0
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Is Protein-Anabolic in Chronic Renal Failure Patients

Abstract: Abstract. To examine the protein anabolic actions of insulin in chronic renal failure, the authors measured four sets of whole body leucine fluxes during insulin alone and insulin with amino acid infusion in nine uremic patients before hemodialysis (B-HD). Seven were restudied 8 wk after initiation of maintenance hemodialysis (HD). Six normal subjects served as control (N). All values ( mol/kg/h, mean Ϯ SEM) are presented in the sequence of B-HD, HD, and N, and only P Ͻ 0.05 are listed. During Flux 1 (baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
3
20
0
2
Order By: Relevance
“…They found that feeding during dialysis resulted in reduced proteolysis, increased protein synthesis, and a change in net protein balance from negative to positive values. It is important to note here that insulin secretion after meal ingestion and insulin-induced protein anabolism both are intact in the ESRD patients (29,30).…”
Section: Hd Is Protein-catabolic: a Discussionmentioning
confidence: 98%
“…They found that feeding during dialysis resulted in reduced proteolysis, increased protein synthesis, and a change in net protein balance from negative to positive values. It is important to note here that insulin secretion after meal ingestion and insulin-induced protein anabolism both are intact in the ESRD patients (29,30).…”
Section: Hd Is Protein-catabolic: a Discussionmentioning
confidence: 98%
“…Fasting resulted in insulin suppression, which should stimulate eating. More importantly, feeding led to a remarkable increase in insulin secretion, the latter making anabolism possible (19).…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid utilization for protein synthesis is impaired in patients with chronic renal failure (11). Anabolic response to amino acid infusion, however, was restored by concomitant administration of insulin (10,32), possibly through augmentation of intracellular amino acid transport (3).…”
mentioning
confidence: 99%